Adsorption Behaviors of Different Water Structures on the Fluorapatite (001) Surface: A DFT Study - Cui, Weiyong; Song, Xueli; Chen, Jianhua; Chen, Ye; Li, Yuqiong; Zhao, Cuihua (Frontiers in Materials, 2020)
To investigate the effect of hydration behavior on the fluorapatite structure, single H2O molecule and three-layer water cluster adsorptions on the fluorapatite (001) surface were performed by means of density functional theory. The results show that a single H2O molecule can form stable chemisorption structures with the fluorapatite (001) surface in the form of single-site, two-site, and three-site adsorption and that the corresponding adsorption energies are 64.817, 98.712, and 139.620 kJ/mol, respectively. The interacting length of the Ca atom and the O atom of the H2O molecule is close to the length of the Ca–O bond in the bulk, and their overlap is mainly contributed by the O 2p and Ca 4s states. The fluorapatite (001) surface shows serious hydration reconstruction after adsorbing three layers of water molecules; these atoms in the surface layer are highly distorted, and the Ca and the PO4 are shifted in opposite directions along the z-axis direction. Further analysis shows that these surface Ca atoms are critical to the hydration behaviors of the transition area, as they can bind strongly to the H2O molecules, with the newly formed Ca–O bonds being between 2.164 and 2.486 Å.